Effect of precursor on growth and morphology of MoS2 monolayer and multilayer. (December 2015) - Ganorkar, Shraddha; Kim, Jungyoon; Kim, Young-Hwan; Kim, Seong-II
Abstract: The rise of two-dimensional (2D) material is one of the results of successful efforts of researchers which laid the path to the new era of electronics. One of the most exciting materials is MoS2 . Synthesis has been always a major issue as electronic devices need reproducibility along with similar properties for mass productions. Chemical vapor deposition (CVD) is one of the successful methods for 2D materials including graphene. Furthermore, the choice of starting materials for Mo and S source is crucial. The different source has different effects on the layers and morphology of MoS2 films. In this work, we have extensively studied the CVD technique to grow few layers of MoS2 with two precursors MoO3 and MoCl5, show remarkable changes. The MoO3 source gives a triangular shaped MoS2 monolayer while that of MoCl5 can achieve uniform MoS2 without triangle. The absence of geometric shapes with MoCl5 is poorly understood. We tried to explain with MoCl5 precursor, the formation of continuous monolayer of MoS2 without any triangle on the basis of chemical reaction formalism mostly due to one step reaction process and formation of MoS2 from gas phase to the solid phase. The film synthesized by MoCl5 is more continuous and it would be a good choice for device applications. Highlights: Monolayer of MoS2 were grown using two different precursors, MoO3 and MoCl5 . MoO3 need a seed to grow monolayer of MoS2 . (two step reaction) Two step chemical reaction gives geometrical shapes monolayer. MoCl5 and S is possibly one step reaction results in formation of Mos2 . In case of MoCl5 it is possible to get uniform MoS2 monolayer.